Identification of a Patient Suitable for CAR-T Cell Therapy in the Outpatient Setting: A Vodcast and Case Example - Ronan Foley; John Kuruvilla (Oncology and Therapy)
Abstract Chimeric antigen receptor T cell (CAR-T) therapies targeting the CD19 antigen have been associated with high and durable response rates in patients with diffuse large B cell lymphoma (DLBCL). CAR-T cell therapies are commonly administered in the inpatient setting due to the average onset of cytokine release syndrome within the first 3 days post infusion, but there has been growing interest in delivering CAR-T cell therapies in the outpatient setting to overcome frequent hospital bed shortages and the high cost of inpatient care. Although this approach could improve access whilst catering to patient preference, it requires a multidisciplinary approach as well as careful patient selection. Herein, Dr. Foley and Dr. Kuruvilla discuss the case of a patient presenting with the ideal profile for CAR-T cell therapy referral whilst also determining the key attributes for eligibility from a clinician’s perspective. Solutions for successful outpatient management include proper education, caregiver support, and early referral to ensure a timely infusion. In conclusion, outpatient administration of CAR-T cell therapy in patients with DLBCLs should be assessed on a case-by-case basis. A vodcast feature is available for this article.